The study on Grossman’s Life and Fate in China: history and present advance - Qingle Wang (RUDN Journal of Studies in Literature and Journalism, 2023)
The author attempts to systematize and summarize the review works of Chinese philologists devoted to Grossman’s Life and Fate . Different Chinese translation versions of the novel are listed and two stages and three aspects of the study on this novel in China are elaborated. The author describes how the study on Life and Fate has developed in China, how scholars in Chinese academic circles view this novel, and what place this novel occupies in Chinese literary criticism. It is concluded that the study of Life and Fate began early enough in China and nowadays is experiencing a new rise. However, Chinese scholars should hold their own point of view on Grossman’s works instead of following Russian or Western scholars’ viewpoint.